2008
DOI: 10.1002/pssa.200778645
|View full text |Cite
|
Sign up to set email alerts
|

Low noise characteristics of AlGaInN‐based self‐pulsating laser diodes

Abstract: We have successfully realized practical self‐pulsating laser diodes (SP‐LDs) based on AlGaInN systems that exhibit low noise characteristics even with an optical feedback of 1% at a high temperature of 75 °C. Our fabricated SP‐LD employs a saturable absorber layer (SAL). We adopt new approaches to realize practical SP operation; specifically, (i) we inserted an AlGaN layer between the active layer and the SAL in order to reduce the threshold current, and (ii) we intentionally introduced reactive ion etching (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Nonhomogeneous distribution of the threading dislocations in the growth direction causes bowing of the free-standing GaN Table 1 Summary of bowing radius and curvature, b m calculated from measured FWHM of (0 0 2) o-scan, and b r from Eq. (2) substrates [7,8]. Therefore, decrease in the nonhomogeneous distribution of dislocations on removing the GaN layer from the N-polar face, which removes a large amount of dislocations, is the first reason for the improvement in the bowing of the freestanding GaN substrates by ICP etching.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonhomogeneous distribution of the threading dislocations in the growth direction causes bowing of the free-standing GaN Table 1 Summary of bowing radius and curvature, b m calculated from measured FWHM of (0 0 2) o-scan, and b r from Eq. (2) substrates [7,8]. Therefore, decrease in the nonhomogeneous distribution of dislocations on removing the GaN layer from the N-polar face, which removes a large amount of dislocations, is the first reason for the improvement in the bowing of the freestanding GaN substrates by ICP etching.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, vertical devices could be grown on electrically conductive GaN substrates to reduce current crowding and self-heating effects of devices. Free-standing GaN substrates have been widely used in laser diodes (LDs) [2] and high-power light emitting diodes (LEDs) [3] owing to its low dislocation density and superior thermal electrical properties. Currently, free-standing GaN substrates can be successfully obtained by growing thick GaN film hetero-epitaxially on a foreign base substrate in hydride vapor phase epitaxy (HVPE), and subsequently separating from the original substrate using laser lift-off (LLO) [4], chemical lift-off [5], and self-separation [6].…”
Section: Introductionmentioning
confidence: 99%
“…GaN substrates have great potential in the manufacturing of laser diodes (LD) [1] and high-power light emitting diodes (LEDs) [2] owing to their low dislocation density and superior thermal electrical properties. Currently, GaN substrates are formed by several methods, such as hydride vapor phase epitaxy (HVPE) [3], Na-flux method [4], and ammonothermal method [5].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies concentrated on self-pulsation for applications in optical storage systems since this approach can reduce the optical feedback noise [1--14]. Several pulse generation techniques exist, including gain-switching [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], self-pulsating [18][19][20], mode-locking [7,17,21], and superradiance [22]. Kono et al demonstrated the first gain-switching (GS) operation of a GaN-based LD, producing a peak power of 12 W and 10 W with a pulse duration of 10 ps at 405 nm [15,17].…”
Section: Introductionmentioning
confidence: 99%